Soft template-assisted copper-doped sodium dititanate nanosheet/graphene oxide heterostructure for photoreduction of carbon dioxide to liquid fuels - Lertthanaphol, Napat; Prawiset, Natthanicha; Soontornapaluk, Pornpinun; Kitjanukit, Nutkamol; Neamsung, Wannisa; Pienutsa, Natpichan; Chusri, Kittapas; Sornsuchat, Thirawit; Chanthara, Prowpatchara; Phadungbut, Poomiwat; Seeharaj, Panpailin; Kim-Lohsoontorn, Pattaraporn; et al. (My University, 2022)
Photoreduction of CO2 to a high-value product is an interesting approach that not only captures CO2 but also converts it into other products that can be sold or used in industry. The mechanism for the CO2 conversion relies strongly on photo-generated electrons that further couple with CO2 and form active radicals for the reaction. In this research, we synthesized a heterostructure of copper-doped sodium dititanate nanosheets and graphene oxide (CTGN) following a one-step hydrothermal process with assistance from a sodium hydroxide soft template. The role of the template here is to facilitate the formation of the nanosheets, creating the nanosheet-graphene 2D-2D heterostructure. The heterostructure yields excellent charge mobility and a low charge recombination rate, while the nanosheet-graphene interfaces house active radicals and stabilize intermediates. The CTGN exhibits an outstanding photoactivity in the photoreduction of CO2, producing liquid fuels, including acetone, methanol, ethanol and i-propanol.